PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KUALITAS LABA DENGAN STRUKTUR KEPEMILIKAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2016 - 2019) - Erle Daffa Abhirama; Imam Ghozali (Diponegoro Journal of Accounting, 2021)
This study aims to examine the influence of corporate social responsibility (CSR) relationships and earnings quality and the impact of managerial ownership and institutional ownership on the relation between corporate social responsibility (CSR) relationships and earnings quality. The sample used is manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2019. The approach used is purposive sampling method and the technique to test the hypothesis using multiple regression analysis analisis. The results of the analysis showed that corporate social responsibility (CSR) has a significant negative effect on the earnings quality. However, managerial ownership has no significant effect on the association between corporate social responsibility (CSR) and earnings quality, but institutional ownership shows a significant effect on the relationship between corporate social responsibility (CSR) and earnings quality.